Functional somatic symptoms and psychological states: an electronic diary study. - Burton, C; Weller, D; Sharpe, M (2009)
OBJECTIVE: To investigate the links between functional physical symptoms and psychological states in a sample of patients with persistent medically unexplained symptoms. Despite the epidemiological evidence for links between physical symptoms and mental processes, prior diary studies have shown inconsistent associations and generally been limited to single symptom and psychological variable pairs. METHODS: Twenty-six patients with at least three functional physical symptoms completed twice daily self-report measures of symptoms, fatigue, anxiety, stress, mood, and symptom concern using electronic diaries over 12 weeks. Associations between physical symptoms and psychological variables were measured by linear mixed effects models at the levels of diary entry and individual. RESULTS: Despite high baseline questionnaire scores for depression and anxiety, diary ratings of anxiety and stress were relatively low. Fixed effects regression coefficients varied between symptoms and psychological variables; for instance, the fixed effects regression coefficient (95% Confidence Intervals) for fatigue as the outcome variable was 0.39 (0.31-0.47) with low mood and 0.05 (-0.01-0.10) with stress as the predictor. Random effects coefficients showed less variation between individuals for fatigue and musculoskeletal pain than for other symptoms. CONCLUSION: Self-reported mood and symptom concern were more strongly associated with functional physical symptoms than anxiety or stress. We suggest that one reason patients with functional somatic symptoms reject psychosomatic explanations is because they do not experience sufficient correlation between symptoms and psychological states.